2017
DOI: 10.3390/w9020080
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Aquaponics Approaching the European Market: To Consumers’ Perceptions of Aquaponics Products in Europe

Abstract: Abstract:The first commercial aquaponics companies are starting up in Europe. The main focus has been on solving technology issues and optimizing production. However, increasing attention is now being paid to certification and regulations linked to aquaponics, as well as the marketing of products and services. The paper presents the results of a study whose main aim was to estimate consumers' knowledge about aquaponics and their acceptance of aquaponics products in different European regions. An on-line questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 38 publications
5
85
0
Order By: Relevance
“…This study echoes several findings from Miličič et al's work [16], which called for an educational campaign of guided tours, workshops, and tastings to enable interaction with a new technology. As UA experts, the participants were able to elaborate on barriers and concerns that might be perceived by the public, and generate creative options for structural operations of aquaponics systems.…”
Section: Discussionsupporting
confidence: 88%
“…This study echoes several findings from Miličič et al's work [16], which called for an educational campaign of guided tours, workshops, and tastings to enable interaction with a new technology. As UA experts, the participants were able to elaborate on barriers and concerns that might be perceived by the public, and generate creative options for structural operations of aquaponics systems.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were obtained in a hypothetical survey in Taiwan (Huang, Kan, & Fu, ), where the authors compared Willingness To Pay (WTP) for “hydroponically grown vegetables” with conventional vegetables. However, in this study, it was also emphasized that the hydroponic alternative was “free of pesticide residues.” On the other hand, the recent study by Coyle and Ellison () on a sample of U.S. lettuce consumers, found a higher WTP premium for “field grown” lettuce over lettuce grown in a “vertical farm” or in a “greenhouse.” Recently, a few studies in Europe and in the United States focused attention on consumers’ perception of aquaponics, which combines hydroponics and aquaculture (the raising of fish) (Miličić, Thorarinsdottir, Santos, & Hančič, ; Short et al., ; Tamin, Harun, Estim, Saufie, & Obong, 2015; Zugravu et al., ). Generally, it was observed that consumers had positive attitudes toward vegetables grown in aquaponic systems, especially because of environmental advantages related to the adoption of this production method.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, consumers do recognize socio-economic benefits from aquaculture and are concerned with sustainability issues (Whitmarsh & Palmieri 2009, Barrington et al 2010, Fernandez-Polanco & Luna 2012. Aquaponics, for example, is regarded as the fittest land-based IMTA for sustainable urban farming (Specht et al 2014), and a European consumer survey about that mode of production found a positive attitude towards local products (Milicic et al 2017). In the same study, willingness to pay regarding food was mostly based on price and whether the products are free of antibiotics, pesticides and herbicides.…”
Section: Present Setbacks and Future Opportunitiesmentioning
confidence: 99%